2000
DOI: 10.1093/ajcn/71.2.637s
|View full text |Cite
|
Sign up to set email alerts
|

Weight loss in Alzheimer disease

Abstract: Nutritional education programs for the caregivers of AD patients seem to be the best way to prevent weight loss and improve the nutritional status of these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
148
0
23

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 221 publications
(177 citation statements)
references
References 39 publications
6
148
0
23
Order By: Relevance
“…Nearly half of the GLD residents had a BMI 23. According to the NuSc more than half were classified as malnourished or being at risk for PEM, a finding in line with several previous reports (Sandman et al, 1987;Burns et al, 1989;Carver & Dobson, 1995;Gillette-Guyonnet et al, 2000).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Nearly half of the GLD residents had a BMI 23. According to the NuSc more than half were classified as malnourished or being at risk for PEM, a finding in line with several previous reports (Sandman et al, 1987;Burns et al, 1989;Carver & Dobson, 1995;Gillette-Guyonnet et al, 2000).…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, more sensitive instruments may have had been able to register the small signs of improvement that were noted by relatives and personnel. Previous studies have shown a decrease of about 3 points in MMSE per year in people with AD (Corey-Bloom et al, 1993;Gillette-Guyonnet et al, 2000). The decrease in MMSE in GLD-I may reflect this expected deterioration.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…A BMI <22 kg/m 2 has been used to screen for undernutrition in older patients and is associated with several chronic conditions, including dementia [26]. Patients in this category in the present sample were six times more likely to access health services for hypoglycaemia than those with greater BMI.…”
Section: Discussionmentioning
confidence: 68%
“…Weight loss is a frequent complication of AD and occurs in 30-40% of patients at all stages [2]. It is associated with faster progression of dementia and with nursing home placement [3].…”
mentioning
confidence: 99%